Mental Health Literacy Scale Arabic Version: A Validation Study Among Saudi University Students - Alshehri, Elham; Alosaimi, Dalyal; Rufaidi, Ebtisam; Alsomali, Nesreen; Tumala, Regie (Frontiers in Psychiatry, 2021)
Mental health problems significantly affect students’ university education. However, studies about mental health literacy (MHL) among Saudi university students are very limited. The twofold objective of this study is to validate an Arabic version of the Mental Health Literacy Scale (MHLS) and assess the MHL of university students. The study participants involved 339 female students. Psychometric evaluation of the MHLS–Arabic version was conducted, and correlation and regression analyses were performed. The scale was successfully cross culturally adapted and found to be valid and reliable. The highest MHL indicator was the students’ perception of confidence in using a computer or telephone to inquire about mental illness data. Conversely, the lowest MHL indicator was the student’s disagreement with the notion that mental infirmity is not an actual medical challenge. Marital status, college attended and academic level were found to have statistically significant effects on the MHL of university students. The Arabic version of the MHLS validly and reliably assessed MHL. This work adds to existing evidence for assessing MHL and can help administrators formulate better strategies to improve the MHL of university students.